2018
DOI: 10.3390/ani8100173
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Stress Susceptibility of Broiler Chickens by Supplementing a Yeast Fermentation Product in the Feed or Drinking Water

Abstract: Simple SummaryPoultry are susceptible to stress induced as a response to common management practices such as vaccination, feed withdrawal, and rearing on reused litter as well as severe stressors such as high environmental temperature. These stressors can result in economic costs to producers that are associated with poor growth and disease. Functional metabolites in the yeast fermentation product Original XPCTM have previously shown positive effects on growth performance and immune function in a variety of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
3
20
1
Order By: Relevance
“…Similar results have also been reported in heat-stressed broilers ( Price et al., 2018 ). Previous studies reported lower ASYM in broilers supplemented with yeast fermentate in the feed or drinking water and exposed to many of the same stressors used in this experiment ( Nelson et al., 2018 ). However, in this study there were no treatment differences in ASYM.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Similar results have also been reported in heat-stressed broilers ( Price et al., 2018 ). Previous studies reported lower ASYM in broilers supplemented with yeast fermentate in the feed or drinking water and exposed to many of the same stressors used in this experiment ( Nelson et al., 2018 ). However, in this study there were no treatment differences in ASYM.…”
Section: Discussionmentioning
confidence: 53%
“…There is also evidence that adding yeast fermentate to either the feed or drinking water improves small intestine histomorphology in Pekin ducks exposed to cyclic heat stress ( Nelson and Archer, 2019 ). In addition, yeast fermentate has been shown to reduce measures of short-term and long-term stress in heat-stressed turkeys ( Bartz, 2016 ) and broiler chickens ( Price et al., 2018 ), and in broilers exposed to acute or rearing stress ( Nelson et al., 2018 ). It has been proposed that the metabolites in yeast fermentation products may help balance the immune and stress responses ( Firman et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental approach used in the present study was not designed to determine which compound in the blend directly impacted heterophil function. There are studies that evaluate specific organic acids and natural compounds, but most of those trials tend to monitor cell numbers in the form of the heterophil:lymphocyte ratio ( Jazi et al., 2018 , Nelson et al., 2018 , Salah et al., 2018 ) instead of actual cell function as we measured in this study. Collectively, the findings of this study suggest that dietary supplementation from a very young age could provide immunological benefits to the bird in the form of early immunomodulation of PBL, including heterophils.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations [70][71][72] Microbial or virus challenges [73][74][75][76][77][78] Gut dis-bacteriosis [79][80][81][82][83] Pipping and hatching [5,84,85] A growing body of evidence clearly indicates that oxidative stress is involved in most of commercially relevant stresses in poultry production (for review see [1,2,15,60,86]).…”
Section: Internal Stressorsmentioning
confidence: 99%